Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Florida)--Spotted seatrout - Johnson, Darlene R. (U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.43)